Mirror Image of Spontaneous Intracranial Hemorrhage - Xiao Dong; Yuanyuan Liu; Xuehong Chu; Erlan Yu; Xiaole Jia; Chuanjie Wu (Diagnostics, 2024)
In this paper, we reported the first case of mirrored spontaneous intracranial hemorrhage with almost identical hematoma morphological characteristics. This patient’s first symptom was loss of consciousness, without any local neurological symptoms. This clinical presentation fits well with the atypical computed tomography (CT) image showing bilateral hematomas, and indicates that the distribution of hypertensive vascular damage may be symmetric and that the degree of the bilateral lesions may be similar.